A Data-Driven Scale-Invariant Weighted Compact Nonlinear Scheme for Hyperbolic Conservation Laws (Communications in Computational Physics, 2024)
With continuous developments in various techniques, machine learning isbecoming increasingly viable and promising in the field of fluid mechanics. In thisarticle, we present a machine learning approach for enhancing the resolution and robustness of the weighted compact nonlinear scheme (WCNS). We employ a neuralnetwork as a weighting function in the WCNS scheme and follow a data-driven approach to train this neural network. Neural networks can learn a new smoothnessmeasure and calculate a weight function inherently. To facilitate the machine learning task and train with fewer data, we integrate the prior knowledge into the learningprocess, such as a Galilean invariant input layer and CNS polynomials. The normalization in the Delta layer (the so-called Delta layer is used to calculate input features)ensures that the WCNS3-NN schemes achieve a scale-invariant property (Si-property)with an arbitrary scale of a function, and an essentially non-oscillatory approximation of a discontinuous function (ENO-property). The Si-property and ENO-propertyof the data-driven WCNS schemes are validated numerically. Several one- and two-dimensional benchmark examples, including strong shocks and shock-density waveinteractions, are presented to demonstrate the advantages of the proposed method.